Shifting waterscapes: explaining basin closure in the Lower Krishna Basin, South India - Venot, Jean-Philippe; Turral, Hugh; Samad, Madar; Molle, Francois (International Water Management Institute, 2007)
Progressive agricultural and water development in the Krishna Basin in South India has led to a rising over commitment of water resources and signs of basin closure are apparent during dry periods. As human consumptive uses are approaching the limits of water availability, this report focuses on the Lower Krishna Basin that bears the brunt of any intervention upstream. Capturing the process of basin closure requires an understanding of the political dimension of access to water and the scope for change. As basin closure intensifies the interconnectedness of ecosystems and water users, adjustments and management decisions result in spatial re-appropriation of water and basin-wide strategies for water management and development that start with the definition and the implementation of water allocation mechanisms are increasingly needed.